Perception of muslim consumers towards tax deduction through Zakat in malaysia: an empirical investigation on muslims in Malaysia - Al-Mamun, Abdullah; Haque, A. K. M. Ahasanul (2015)
The aim of this study is to explore the factors which are affecting Muslim consumers‟ perception towards tax deduction through zakat in Malaysia. A conceptual framework was drawn based on the literature. Six factors were extracted through principal component analysis and SEM was run to test the hypotheses. This research found that halal-haram aspect of Islamic Shariah has a very positive influence on Muslim consumers‟ perception towards the tax rebate system. In addition, legal consciousness and knowledge about tax and zakat have positive significant impact on Muslim consumers‟ perceptions towards this system. Due to the limited literature available on this subject matter, this study offers unique findings that may help in capitalizing the practices in Muslim countries and to understand their consumers‟ perception regarding the tax deduction system. In conclusion zakat institutions in Malaysia will also be better benefitted through this research finding.